Psoriatic Arthritis: A Case Study - Dr.G.D.Pol, Vd. Snehal Dilip Yadav, Vd. Jai Kiran Kini (International Journal of Innovative Research in Medical Science, 2016)
Psoriatic Arthritis requires a special mention as it may develop in up to 30 percent of people who have the chronic skin condition Psoriasis. Anyone who has psoriasis and joint pain may have psoriatic arthritis. Genetics, dietary, lifestyle related, environmental and behavioral/psychological factors play major role in pathogenesis. Vitiation of all three doshas is major contributing factor in the manifestation of the disease. Ayurveda advocates holistic approach of shodhana, internal drug administration (shamana) and external application in the treatment protocol. In this article, a patient treated with similar treatment protocol is presented as a case study.